1996
DOI: 10.1177/000456329603300201
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cigarette Smoking and Alcohol Consumption on Blood Lipids: A Dose-Related Study on Men

Abstract: The separate and joint effects of cigarette smoking and alcohol consumption on serum concentrations of total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and triglycerides were investigated in 46 750 men attending the BUPA Health Screening Centre in London during the period 1983–1987, after allowing for differences in age, body mass index and exercise level. Drinking alcohol was found to raise both total cholesterol and HDL-C concentrations, in such a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 13 publications
9
78
0
1
Order By: Relevance
“…However, the proportion of cholesterol subfractions may be a more relevant indicator of cardiovascular disease risk. The positive association of alcohol consumption and HDL/total cholesterol ratio observed in this study corresponds to findings observed by others, although there are differences in the strength of the effect (Whitehead et al, 1996;Dimmitt et al, 1998;Nanchahal et al, 2000). …”
Section: Discussionsupporting
confidence: 90%
“…However, the proportion of cholesterol subfractions may be a more relevant indicator of cardiovascular disease risk. The positive association of alcohol consumption and HDL/total cholesterol ratio observed in this study corresponds to findings observed by others, although there are differences in the strength of the effect (Whitehead et al, 1996;Dimmitt et al, 1998;Nanchahal et al, 2000). …”
Section: Discussionsupporting
confidence: 90%
“…At first glance, an increased response to a pathological state (heavy smoking) appears anomalous. One possible explanation is related to hematocrit, which is elevated in heavy smokers (Whitehead et al, 1995), as is blood viscosity (Lowe et al, 1980). Increased hematocrit has been associated with elevated BOLD responses (Levin et al, 2001;Gustard et al, 2003).…”
Section: Discussion Of Visual Activation Resultsmentioning
confidence: 99%
“…Moreover, chronic smoking is linked in several ways to hypertension (Kochar and Bindra, 1996), and to the development of diabetes (Eliasson, 2003). Furthermore, cigarette smoking causes increases in hematocrit and hemoglobin concentration (Whitehead et al, 1995) and blood viscosity (Lowe et al, 1980). Since a number of these effects have been shown to impact the BOLD fMRI signal (Hamzei et al, 2003;Levin et al, 2001;Gustard et al, 2003;Wessels et al, 2006), it was important to look for a potential relationship between the BOLD response to activation tasks and smoking history.…”
Section: Introductionmentioning
confidence: 99%
“…In the tables a smoker is defined as a person currently smoking at least one cigarette per day. Smoking affects the blood lipid profile: serum HDL and LDL cholesterol concentrations have been reported to be lower and higher, respectively, in smokers than in nonsmokers [4]. After cessation of smoking, HDL is observed to increase [5].…”
Section: Smokingmentioning
confidence: 99%
“…Smoking affects the blood lipid profile: serum HDL and LDL cholesterol concentrations have been reported to be lower and higher, respectively, in smokers than in nonsmokers [20] [21]. On the other hand, moderate alcohol consumption is known to lower the incidence of coronary heart disease [22].…”
Section: Association Of Smoking and Alcohol Drinkingmentioning
confidence: 99%